Rev-Erbα: A Chronobiological Approach to Inflammation and Lung Disease Management: A Comprehensive Review - Mateen, Sayyed; Qureshi, Aafreen; Sharma, Amit; Gupta, Vikas (Indian Journal of Pharmacy Practice)
The circadian cellular clock partially reduces macrophage inflammatory response by interacting with the nuclear receptor Rev-erbα. Disruption of circadian rhythm can result in diabetes, metabolic issues and fibrosis. Rev-Erb clock repressor is expressed in the brain, skeletal muscles, liver, heart & lungs. Rev-Erb reduces lung fibrosis and inflammation by acting on NF-κB. Agonists of Rev-Erb lead to a decrease in fat mass specifically in adipose tissue. These agonists also reduce pulmonary fibrosis by preventing myofibroblast differentiation in the lung. A decrease in REV-ERBα levels makes the lungs more sensitive to pro-fibrotic triggers, worsening fibrosis progression. Overproduction of collagen as well as lysyl oxidase due to TGFβ can be stopped by GSK4112, an agonist of Rev-erbα in human lung fibroblasts while an opposite impact is shown by the antagonist. Progression of Lung Adenocarcinoma is contributed by the downregulation of REV-ERBα. Agonists of REV-ERBα such as SR9009 and GSK4112, have therapeutic potential in reducing lung inflammation caused by cigarette smoke-induced COPD. GSK4112 (agonist) and GSK1362 (inverse agonist) target REV-ERBα to reduce pulmonary inflammation, with GSK1362 offering superior efficacy by stabilizing REV-ERBα protein. Based on these findings, there is hope for the therapeutic development of Rev-Erbα agonists for lung fibrosis, thus, further research and clinical trial.
Keywords: Circadian rhythm; COPD; Fibrosis; Inflammation; Rev-Erbα